Mourning companion animals : guiding clients from loss to legacy - Stone, Susan Dowd (New York, NY : Routledge, 2024)
"Mourning Companion Animals is a guidebook for mental health clinicians searching for effective, compassionate resources to guide their clients through the often-devastating experience of animal companion loss. Chapters offer powerful and comprehensive strategies to heal animal companion loss based in sound, evidenced based, theoretical perspectives. The included author-generated inventory, the animal companion bereavement questionnaire, provides further assistance in clinician exploration of each client's unique bond with their lost companion. The book's content is the result of more than twenty-five of extensive work within the human-animal bond, clinical training in the referenced therapies, and application of major psychodynamic theories"--
Keywords: Pet owners -- Psychology; Pet loss; Pets -- Death; Bereavement -- Psychological aspects; PSYCHOLOGY / Mental Health; SOCIAL SCIENCE / Social Work